Acute Effects of Inspiratory Loads and Interfaces on Breathing Pattern and Activity of Respiratory Muscles in Healthy Subjects - da Fonsêca, Jéssica Danielle Medeiros; Resqueti, Vanessa Regiane; Benício, Kadja; Fregonezi, Guilherme; Aliverti, Andrea (Frontiers in Physiology, 2019)
Objectives: The aim of this study was to evaluate the acute effects of different inspiratory loads and different interfaces on the breathing pattern and activity of the respiratory muscles. Methods: Twenty healthy adults were recruited and assigned to two groups (20% and 40% of the Maximal Inspiratory Pressure) by way of randomized crossover allocation. Subjects were evaluated during quiet breathing, breathing against inspiratory load, and recovery. The measurements were repeated using two different interfaces (nasal and oral). Chest wall volumes and respiratory muscle activity were assessed with optoelectronic plethysmography and surface electromyography, respectively. Results: During the application of inspiratory load, significant changes were observed in the respiratory rate (p < 0.04), inspiratory time (p < 0.02), minute ventilation (p < 0.04), tidal volume (p < 0.01), end-inspiratory volume (p < 0.04), end-expiratory volume (p < 0.03), and in the activity of the scalene, sternocleiomastoid, and parasternal portion of the intercostal muscles (RMS values, p < 0.01) when compared to quiet breathing, regardless of the load level or the interface applied. Inspiratory load application yielded significant differences between using nasal and oral interfaces with an increase in the tidal volume (p < 0.01), end-inspiratory volume (p < 0.01), and electrical activity of the scalene and sternocleiomastoid muscles (p < 0.01) seen with using the nasal interface. Conclusion: The addition of an inspiratory load has a significant effect on the breathing pattern and respiratory muscle electrical activity, and the effects are greater when the nasal interface is applied.